1995
DOI: 10.1159/000227465
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Study of Low-Dose Subcutaneous lnterleukin-2 Plus Melatonin versus Supportive Care Alone in Metastatic Colorectal Cancer Patients Progressing under 5-Fluorouracil and Folates

Abstract: Chemotherapy with 5-fluorouracil (5-FU) and folates represents the first-line standard therapy for metastatic colorectal cancer, whereas at present there is no conventional second-time treatment. Because of its importance in generating an effective anticancer immune response, interleukin-2 (IL-2) could constitute a new promising therapy of advanced colon cancer. Generally, IL-2 may determine tumor regressions in colon cancer only when it is given at high toxic doses. Our preliminary studies have shown that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(33 citation statements)
references
References 6 publications
0
31
0
1
Order By: Relevance
“…(19,20,21,22,23,11,24,25,26,27,28,29,30,31,32,33) Three independent randomized trials, including this trial, have been run. (34,35) It is noteworthy that all of the trials from Lissoni and colleagues have had positive outcomes and, as of yet, there have been no confirmatory publications from outside of his group.…”
Section: Discussionmentioning
confidence: 99%
“…(19,20,21,22,23,11,24,25,26,27,28,29,30,31,32,33) Three independent randomized trials, including this trial, have been run. (34,35) It is noteworthy that all of the trials from Lissoni and colleagues have had positive outcomes and, as of yet, there have been no confirmatory publications from outside of his group.…”
Section: Discussionmentioning
confidence: 99%
“…The use of IL-12, either as a preoperative treatment or in metastatic colorectal cancer is claimed to be associated with an improved survival (compared to current best supportive care) (Barni et al, 1995;Brivio et al, 1996). Reithmuller and colleagues reported that a monoclonal antibody (17-1A) to a colorectal antigen resulted in an improved survival for patients with Dukes' stage C colon cancer when given post resection (Reithmuller et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…This was selected principally, as the supportive care arm represented the appropriate group for the comparator of ASC/BSC where 31% of the patients had received ASC. Two other trials of chemotherapy in the second/subsequent-line treatment vs supportive care for of metastatic CRC (Barni et al, 1995;Rao et al, 2004) were considered inappropriate proxies in this analysis as the supportive care arms comprised BSC alone and no ASC. Of note, survival figures differed between these studies such that use of alternative studies may have led to different cost-effectiveness outcomes such as cost per QALY.…”
Section: Discussionmentioning
confidence: 99%